Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10517-005-0430-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells from Human Bone Marrow and Adipose Tissue: Isolation, Characterization, and Differentiation Potentialities

Abstract: Comparative study of cultured human bone marrow and adipose tissue (lipoaspirate) mesenchymal stem cells was carried out. The main morphological parameters, proliferative activity, expression of surface and intracellular markers of these cells were characterized. Flow cytofluorometry and histological staining showed that both cell types exhibited similar expression of CD105, CD54, CD106, HLA-I markers, were positively stained for vimentin, ASMA, collagen-1, and fibronectin, but not HLA-DR, CD117, and hemopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(116 citation statements)
references
References 18 publications
(43 reference statements)
6
104
0
4
Order By: Relevance
“…As indicated in Table 1, mRNA expression of several of these protein markers was confirmed by real-time quantitative PCR analysis (data not shown). These findings are in agreement with reports made for adipose-derived stromal cells from humans, rodents, and non-human primates (Safford, Hicok et al 2002;Zuk, Zhu et al 2002;Ashjian, Elbarbary et al 2003;Safford, Safford et al 2004;Fujimura, Ogawa et al 2005;Romanov, Darevskaya et al 2005;Ning, Lin et al 2006). …”
Section: Morphological Differentiation and Expression Of Neuro-glial supporting
confidence: 93%
“…As indicated in Table 1, mRNA expression of several of these protein markers was confirmed by real-time quantitative PCR analysis (data not shown). These findings are in agreement with reports made for adipose-derived stromal cells from humans, rodents, and non-human primates (Safford, Hicok et al 2002;Zuk, Zhu et al 2002;Ashjian, Elbarbary et al 2003;Safford, Safford et al 2004;Fujimura, Ogawa et al 2005;Romanov, Darevskaya et al 2005;Ning, Lin et al 2006). …”
Section: Morphological Differentiation and Expression Of Neuro-glial supporting
confidence: 93%
“…First, ASCs can be easily obtained from adipose tissues and maintained in stable growth and proliferation (42,44). Second, they can be differentiated into adipogenic, osteogenic, chondrogenic, neurogenic, or myogenic lineages (21,38,39,44). Third, ASCs secrete various cytokines such as interleukin-6 and growth factors such as basic fibroblast growth factor (bFGF), hepatocyte growth factor, and insulin-like growth factor (IGF), which are involved in muscle satellite cell activation and regeneration (7).…”
Section: Introductionmentioning
confidence: 99%
“…It was easy to separate the slurry of tissue into adipose and stromal cells during the process of centrifugation. As early as in the first stages of the study, it was shown that the capability of the cells to adhere was higher with this method than with enzyme incubation [17]. Researchers are still looking for more efficient methods of obtaining stem cells from the stromal fraction.…”
Section: Methods Of Isolating Adscsmentioning
confidence: 99%
“…Furthermore, they are positively stained for the presence of vimentin, ASMA, collagen (collagen-1) and fibronectin, but they do not include HLA-DR, CD117 or hematopoietic cell markers [17]. ADSCs are generally similar but not identical to BMSCs.…”
Section: The Phenotype Of Adscsmentioning
confidence: 99%